A combination formula transfer device for roe - GUO FUHUA; LIU YONGFU; CHEN YONG (2016)
The utility model discloses a combination formula transfer device for roe, including the circular shape plate body, evenly set up a plurality of mounting holes on the plate body, be provided with spherical structure's housing in every mounting hole, be provided with roe import and mesh on the housing, the external diameter of mesh is less than the external diameter of roe, the plate body middle part is connected with rustless steel chain, rustless steel chain's tip is provided with the link. The utility model discloses a can experimental efficiency have been improved simultaneously to a plurality of experimental group experiment, secondly external impurity and the influence of temperature to the roe can be reduced in the roe transfer process. 本实用新型公开了种用于鱼卵的组合式转移装置，包括圆形的板体，所述板体上均匀开设有多个安装孔，每个安装孔内设置有球形结构的罩壳，所述罩壳上设置有鱼卵进口和网孔，网孔的外径小于鱼卵的外径，所述板体中部连接有不锈钢链，所述不锈钢链的端部设置有挂环。本实用新型是能够同时对多个实验组进行实验，提高了实验效率，二是能够在鱼卵转移过程中减少外界杂质及温度对鱼卵的影响。